Sistem panggilan dalam dialek melayu Kampung Air - Fatimah Haji Damit (Brunei : Dewan Bahasa dan Pustaka Brunei, Kementerian Kebudayaan, Belia dan Sukan, 2008)
Sociolinguistic aspects of honorific system, pronoun, and term of address used in Malay family of water villages in Brunei.
Bibliografi : p. 82-84.
Keywords: Malay language -- Dialects -- Brunei; Malay language -- Address, Forms of; Malay language -- Style; Brunei -- Malay language -- Dialects